Developing students' reading ability using visual novel for high school students - Rizky Aditya Prasetyo; Rahayu Kuswardani (Journal of Research on English and Language Learning (J-REaLL), 2021)
Recently, many students study from home and their class is conducted online. Many of them spend more time at home, and since their class is conducted online, most of the students have their smartphones. Because of this situation, the visual novel can be used to aid the students in studying English, especially for reading. The visual novel is a game that utilizes pictures with various sound effects to make the reader more interested in playing and watching the picture. This study is to develop a visual novel for education with the purpose to aid students in learning English. The research method utilized by the researcher in the development of a visual novel is a DDR (Design and Development) method. The participants in this research were tenth-graders from various schools in Surabaya. The instrument used in this research were questionnaires, structured interviews, and expert validation. The visual novel was validated by the expert before testing the game. This study found that Visual Novel can help students became more motivated to learn English especially reading and the response they gave toward using visual novel in aiding learning English is positive. Several students also struggled with the game due to the student's lack of knowledge. In conclusion, the visual novel has been proven to meet the students' demand to aid in learning English. The implications of these findings are that teachers should use media to create a positive learning environment.